Impact of patients' professional and educational status on perception of an antibiotic policy campaign: a pilot study at a university hospital. (September 2016) - Giannitsioti, Efthymia; Athanasia, Sofia; Plachouras, Diamantis; Kanellaki, Stavroula; Bobota, Fani; Tzepetzi, Georgia; Giamarellou, Helen
Highlights: Remarkable rates of personal accountability on antibiotic misuse. Sex/education/profession influence patients' perceptions of the antibiotic campaign. Targeted antibiotic campaigns can contribute in combating antimicrobial misuse. Abstract: Antibiotics are overused in many European countries, particularly Greece, leading to emerging antimicrobial resistance with sustained high mortality among hospitalised patients. Limited data are available regarding factors influencing people's knowledge and the impact of public campaigns on antibiotic misuse. Patients' beliefs regarding antibiotics were investigated in the outpatient clinic of a university hospital in Athens, Greece. A questionnaire-based survey was conducted to examine patients' opinions on antibiotic use in the waiting room of the outpatient clinic. All participants read an illustrated pocket-sized leaflet endorsed by official authorities on the European Antibiotic Awareness Day (EAAD). Volunteers then completed a questionnaire containing information on demographics, knowledge on antibiotic use and overuse, and remarks on the quality of the leaflet's content. In a logistic regression analysis including age, sex, educational level and professional status of 605 eligible participants, women were more aware [odds ratio (OR) = 3.2, 95% confidence interval (CI) 1.8–5.8; P  < 0.0001] and people with elementary education were less aware (OR = 0.4, 95% CI 0.1–0.9; P  = 0.04) of antimicrobial misuse. Workers were also more aware than retired or unemployed people ( P  = 0.007). However, only 16.0% of participants knew about the EAAD. All participants agreed on antibiotic misuse in Greece, mentioning patient accountability as the main cause (26.8%), an opinion more pronounced in highly educated individuals. In conclusion, targeted interventions taking into account variations in educational level and employee status should be considered in future scheduled educative campaigns on antibiotic overconsumption in highly prescribing antibiotic countries.